Prophylaxis for latent tuberculosis infection in liver transplant recipients - Ertuğrul, Gökhan; Düger, Mustafa (Journal of Surgery and Medicine, 2019)
Aim: Immunosuppressive drugs predispose the liver transplant recipient to reactivation of latent tuberculosis infections. Prophylactic therapies given to these patients are very important for prevention of reactivation. The aim of this study was to evaluate the prophylaxis of latent tuberculosis infections in liver transplant recipients. Methods: We designed a retrospective cohort study. We examined liver transplant recipients Between December 2014 and December 2017 with results of T Spot and prophylactic treatment. Results: Among 143 recipients, positive T Spot results were detected in 21 (14.7%) cases. Twenty one patients received Isoniazid prophylaxis and no reactivation of tuberculosis was detected during follow-up of 48 months. Conclusion: Isoniazid appears to be successful in prophylactic treatment of latent tuberculosis infection in liver transplant recipients.